QUALITY EVALUATION OF A PHYTOPHARMACEUTICAL BY HPTLC AND SCREENING OF ITS IMMUNOSTIMULANT & ANTIMICROBIAL ACTIVITIES - Madhu. C. Divakar; WD Sam Solomon; Dinesh B; Dharma S (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The present work includes the HPTLC quality evaluation of a phytopharmaceutical (immunostimulant & expectorant) formulation prepared from three herbs namely Ocimum sanctum (tulsi), Allium cepa (red onion) and Mentha piperita (mentha) as per the guidelines of Indian Pharmacopoeia Commission, Ministry of Health and family welfare, Govt. of India.  The latest direction of Indian Pharmacopoeia commission indicates for the inclusion of a minimum of four therapeutic or analytical markers in a phytopharmaceutical formulation (PPF). In the present work eugenol, menthol and quercetin were used as the markers for the herbal drugs Ocimum sanctum, Allium cepa and Mentha piperita respectively. The Herbovigillance part of the work can give information specific to herb-drug interactions for the patients taking these kinds of preparations along with conventional drugs in the post covid-19 pandemic period.  Herbovigillance protocols were framed for the patients under anti-diabetic drugs, anti-coagulants, anti-allergic drugs, and anti-hypertensives for monitoring carefully if taking the prepared phytopharmaceutical formulation along with these conventional drugs.The antimicrobial activity studies showed zone of inhibition of 11.8 mm and 10.6mm for E. coli (gram-ve) and Staph.aures (gram +ve) respectively by PPF. The percentage immunostimulation was found to be 64% and 82% for the PPF at the dose of 50mg/ml and100 mg/ml respectively.The HPTLC analysis of the phytopharmaceutical formulation indicated that, an amount of 0.008 mcg of eugenol (Rf value: 0.83), 0.008 mcg of quercetin (Rf value: 0.73), 0.004 mcg of menthol (Rf value: 0.59) are present per mcg of Ocimum sanctum, Allium cepa and Mentha piperita extracts respectively. The results can give an insight for herbal manufacturers for the quality development of phytopharmaceutical formulations